Treatment of Canine Idiopathic Epilepsy - Clinical Picture after Drug Interaction - Ribeiro, Diego; Leite , Amanda Perini; Alvim , Gabriela Rotatori; Costa, Lara Garcia; Chagas , Zayra Siqueira; Silva, Ana Karla de Lima; Pereira, Ana Flávia Silva; Nogueira, Rodrigo Bernardes (Acta Scientiae Veterinariae, 2022)
Background: The large number of diseases demand perennial development of the pharmaceutical industry. The drug-testing phase is essential to make them available safely. Awareness of pharmacological properties, adverse effects and drug interactions is required. Drug interactions are common in veterinary medicine and should be avoided. At times, epileptic seizures require polydrug therapy, predisposing patients to drug interactions. The interaction between carbamazepine and phenobarbital reported in the literature is an example. The aim of this paper is to report a clinical picture of drug interaction in the treatment of idiopathic epilepsy. Case: A 1-year-old Border Collie male dog, was admitted at the Veterinary Hospital of the Federal University of Lavras in post-ictal. The tutor reported that a year ago the animal had epileptic seizures and clusters with intervals of 21 to 25 days. Despite the continued use of previously prescribed phenobarbital (7.4 mg/kg, v.o., BID, until new recommendations) and carbamazepine (7.5 mg/kg, v.o., BID, until new recommendations), seizure control was not achieved. The physical examination indicated, tachypnea, ptialism, mydriasis, intense fatigue, and alienation from the environment. The patient did not respond to the threat-reflex test. Blood count, hepatic and renal blood chemistry, serum electrolyte (potassium, sodium, calcium and phosphorus), and phenobarbital dosages were requested. Based on the animal's history, breed characteristics, and alterations in the physical examination associated with normal results in complementary exams, idiopathic epilepsy was diagnosed. After analyzing the case, it was observed that the inefficiency in the control of seizures was possibly due to the drug interaction between phenobarbital and carbamazepine. Carbamazepine and phenobarbital reciprocally reduce their half-lives. To confirm the raised hypothesis, the serum concentration of carbamazepine was gradually reduced through weaning from its dose administered to the patient. Serial dosage of the concentration of phenobarbital in the bloodstream was performed. As a result, the serum phenobarbital, previously dosed at a concentration of 13.3 mg/dL with concomitant administration of carbamazepine, increased to 22 mg/dL 40 days after the beginning of weaning from carbamazepine (T0), and then to 36 mg/dL 100 days after T0. There was an increase in the concentration of phenobarbital in the bloodstream while the serum concentration of carbamazepine declined. The patient spaced out his seizures to every 50 to 60 days with phenobarbital monotherapy at a dose of 6 mg/kg. Discussion: Efficient control of clusters, such as the reduction of seizures by 50%, was only possible due to the meticulous perception of the possible interaction reported in medicine. Carbamazepine and phenobarbital are P450 isoenzyme inducers. The concomitant administration of both drugs potentiated the action of isoenzymes in the hepatic microsomal system, which led to an accelerated metabolic processing of the drugs. After weaning from carbamazepine, that is, reducing the action of carbamazepine on the isoenzymes of the P450 enzyme system, the concentration of phenobarbital normalized at 36 mg/dL. Such concentration is within the reference range reported in the literature: 25 mg/dL to 35 mg/dL of serum phenobarbital for treatment efficacy. Therefore, the control of convulsive crises was achieved. The increase in the concentration of phenobarbital due only to weaning from carbamazepine, even after decreasing the daily dose of barbiturate prescribed to the animal, contributed to evidence of the interaction of these drugs. It is noted that prior knowledge of pharmacological properties, careful study of the patient's history, and the cooperation of the tutor were essential for the therapeutic success and practice of evidence-based veterinary medicine. Keywords: drug interaction, carbamazepine, phenobarbital, P450 enzyme. Título: Tratamento da epilepsia idiopática canina - quadro clínico após interação medicamentosa. Descritores: interação medicamentosa, carbamazepina, fenobarbital, enzima P450.